THE IMPLEMENTATION OF DIRECT METHOD IN TEACHING ENGLISH FOR 1ST GRADE OF STUDENTS - Raninta Candra Dewi; IGA Lokita Purnamika Utami; Ni Putu Astiti Pratiwi (Lingua Scientia, 2023)
The aim of this study was to describe the implementation of direct method in teaching English in North Bali Bilingual School and the teachers’ perception on the impact of direct method toward students’ learning qualities. The researcher used descriptive qualitative research, the participants who enrolled in this research was teachers that teach English for students of 1st grade in North Bali Bilingual School. There were two English teacher of North Bali Bilingual School who participated in this research. Observation sheet and interview guide were used by the researcher as the instruments. The findings show that the implementation of direct method for students of 1st grade in NBBS is conducted properly under an adjustment to the circumstances of students. The approach used by teachers to teach young learners using Direct Method is phonetic approach. Also, this finding shows that according to the teachers’ perception, direct method has good impact on the learning quality. It can be measured from the consistency of using English in learning process, interesting material according to students’ need and students’ liking, active participation of students and the habit formed as learning achievement from this method.Keywords : Direct method, Perception, Young learners, English learning process